Thrombocytopenia in malaria : who cares? - Lacerda, Marcus Vinícius Guimarães de (2011)
Despite not being a criterion for severe malaria, thrombocytopenia is one of the most common complications of both Plasmodium vivax and Plasmodium falciparum malaria. In a systematic review of the literature, platelet counts under 150,000/mm³ ranged from 24-94% in patients with acute malaria and this frequency was not different between the two major species that affected humans. Minor bleeding is mentioned in case reports of patients with P. vivax infection and may be explained by medullary compensation with the release of mega platelets in the peripheral circulation by megakaryocytes, thus maintaining a good primary haemostasis. The speculated mechanisms leading to thrombocytopenia are: coagulation disturbances, splenomegaly, bone marrow alterations, antibody-mediated platelet destruction, oxidative stress and the role of platelets as cofactors in triggering severe malaria. Data from experimental models are presented and, despite not being rare, there is no clear recommendation on the adequate management of this haematological complication. In most cases, a conservative approach is adopted and platelet counts usually revert to normal ranges a few days after efficacious antimalarial treatment. More studies are needed to specifically clarify if thrombocytopenia is the cause or consequence of the clinical disease spectrum.